Increasing cardiovascular medication adherence: A medical research council complex mhealth intervention mixed‐methods feasibility study to inform global practice. (5th August 2020) - Khonsari, Sahar; Chandler, Colin; Parker, Richard; Holloway, Aisha
Abstract: Aims: To evaluate a mHealth intervention to increase medication adherence among Iranian coronary heart disease patients. Design: Quantitative‐dominant mixed‐methods study. Data Source: Iranian coronary heart disease patients' responses and most recent clinical documents as well as responses from Iranian cardiac nurses who participated in this study. Methods: The study was conducted between September 2015–April 2016 drawing on the Medical Research Council's Framework. Phase one comprised of a patients' survey and focus groups with cardiac nurses. The automated short message service reminder was piloted in phase two. We recruited 78 patients and randomized to receive either 12‐week daily reminders or usual care. The primary outcome was the effect on medication adherence; secondary outcomes were self‐efficacy, ejection fraction, functional capacity, readmission rate and quality of life. Results: Feasibility was evidenced by high ownership of mobile phones and high interest in receiving reminders. Participants in the intervention group showed significantly higher medication adherence compared with the control group. Conclusion: The mHealth intervention was well accepted and feasible with early evidence of effectiveness that needs to be confirmed in a fully powered future randomized clinical trial. Abstract : 目的: 评估mHealth干预措施是否增加伊朗冠心病患者的用药依从性。 设计: 定量为主的混合方法研究。 数据源: 伊朗冠心病患者的反应和最新临床文献以及参与本研究的伊朗心脏护士的反应。 方法: 这项研究是在2015年9月至2016年4月之间根据医学研究委员会的框架进行的。第一阶段包括患者调查和和心脏科护士的焦点小组。第二阶段试行自动短信提醒服务。我们招募了78位患者，随机接受为期12周的每日提醒或常规护理。主要结果是对药物依从性的影响。次要结果是自我效能、射血分数、功能能力、再入院率和生活质量。 结果: 手机拥有率高和收到提醒的兴趣很高，证明了这种方法的可行性。与对照组相比，干预组的参与者显示出更高的药物依从性。 结论: mHealth干预已被广泛接受并且可行，并且有早期有效性证据，需要在完全有力的未来随机临床试验中得到证实。